TIDieR-telehealth: precision in reporting of telehealth interventions used in clinical trials - unique considerations for the Template for the Intervention Description and Replication (TIDieR) checklist - Daniel I. Rhon; Julie M. Fritz; Robert D. Kerns; Donald D. McGeary; Brian C. Coleman; Shawn Farrokhi; Diana J. Burgess; Christine M. Goertz; Stephanie L. Taylor; Tammy Hoffmann (BMC Medical Research Methodology, 2022)
Abstract Background Recent international health events have led to an increased proliferation of remotely delivered health interventions. Even with the pandemic seemingly coming under control, the experiences of the past year have fueled a growth in ideas and technology for increasing the scope of remote care delivery. Unfortunately, clinicians and health systems will have difficulty with the adoption and implementation of these interventions if ongoing and future clinical trials fail to report necessary details about execution, platforms, and infrastructure related to these interventions. The purpose was to develop guidance for reporting of telehealth interventions. Methods A working group from the US Pain Management Collaboratory developed guidance for complete reporting of telehealth interventions. The process went through 5-step process from conception to final checklist development with input for many stakeholders, to include all 11 primary investigators with trials in the Collaboratory. Results An extension focused on unique considerations relevant to telehealth interventions was developed for the Template for the Intervention Description and Replication (TIDieR) checklist. Conclusion The Telehealth Intervention guideline encourages use of the Template for the Intervention Description and Replication (TIDieR) checklist as a valuable tool (TIDieR-Telehealth) to improve the quality of research through a reporting guide of relevant interventions that will help maximize reproducibility and implementation.